2020
DOI: 10.14740/jem632
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium-Glucose Cotransporter 2 Inhibitors on Hepatic Fibrosis in Patients With Type 2 Diabetes: A Chart-Based Analysis

Abstract: Background:The presence of nonalcoholic fatty liver diseases (NAFLDs) and type 2 diabetes was associated with elevated risks of cardiovascular events as well as the progression of NAFLD to fibrosis/cirrhosis and hepatocellular carcinoma. Sodium-glucose cotransporter 2 inhibitor (SGLT2i) is a widely used antidiabetic drug, which promotes urinary excretion of glucose. Recent animal and human studies demonstrated the beneficial effects of SGLT2is on lipid accumulation and fibrosis in the liver. The purpose of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Because we previously reported that SGLT2i improves atherogenic dyslipidemia, liver function and serum UA in addition to glucose-lowering [ 17 , 18 , 19 , 20 ], we analyzed changes in metabolic parameters after the start of pemafibrate by dividing patients into patients who received SGLT2i and patients who did not receive SGLT2i ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we previously reported that SGLT2i improves atherogenic dyslipidemia, liver function and serum UA in addition to glucose-lowering [ 17 , 18 , 19 , 20 ], we analyzed changes in metabolic parameters after the start of pemafibrate by dividing patients into patients who received SGLT2i and patients who did not receive SGLT2i ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a significant decrease in AST was observed only in patients who received SGLT2i. Since SGLT2i improve liver function [ 17 , 18 , 19 , 20 ], synergism and/or the possible interaction between pemafibrate and SGLT2i may be associated with a decrease in AST, which still needs further studies. Accumulated data suggest that NAFLD is induced by abnormal hepatic lipid metabolism such as an increase of intra-hepatic fat content [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies did not find a significant change from baseline in liver fibrosis [ 43 , 69 , 70 ], others reported SGLT2 inhibitors effectively decrease the FIB-4 index. [ 18 , 71 ]. In another study, the APRI index decreased significantly with pioglitazone [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the FIB-4 index, a validated marker of liver fibrosis, several studies found no significant effects compared with baseline or use of other glucose-lowering agents [ 20 , 32 34 ]. Nevertheless, two studies demonstrated a significant reduction in FIB-4 index with SGLT2 inhibitor [ 35 , 36 ]. In our study there were no significant changes in non-invasive parameters according to the NAFLD fibrosis score, FIB-4 index, and APRI.…”
Section: Discussionmentioning
confidence: 99%